A novel fly optimization algorithm for swarming application - Zainal Abidin, Zulkifli; Ngah, Umi Kalthum; Arshad, Mohd Rizal; Ong, Boon Ping (2010)
This paper presents an initial development stage of Fly Optimization Algorithm which will be used for the path planning system of a swarm of autonomous surface vehicles. This algorithm was initially designed to be implemented for a swarm of robots which would be able to locate the deepest portion of lakes. The ability of the robots to reach the designated target points will therefore also be considered.